Dual band antenna designing with composite right/left handed. Issue 4 (April 2015) - Zarrabi, Ferdows B.; Ahmadian, Rahele; Rahimi, Maryam; Mansouri, Zahra
ABSTRACT In this article, dual band antenna by implementation of composite right/left‐handed for UWB and WLAN application is presented with L shape ground. First antenna, has two resonances at 1.8 and 5.2 GHz for GSM 1800 and 5 GHz WLAN indoor application with omnidirectional pattern and It is fabricated on FR‐4 low cost substrate with dielectric constant ε = 4.4 and loss tangent of tan δ = 0.02. In the second antenna, first band support 2.38–2.48 GHz that covers the WLAN with omnidirectional pattern but the second operation band is between 4.18 and 9.85 GHz for covering WLAN and at this frequency, antenna has semidirectional pattern. The second antenna is printed on Taconic TLY‐5 low permittivity substrate with relative permittivity of 2.2. Maximum antenna gain between −2 and 4 dBi but second antenna shows low gain and it is in range of 1.4–3.3 dBi. Albeit, here, the results of simulated antenna design are compared with experimental results. The current distribution shows that how these CRLH cells have helped for change in pattern of antenna. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:774–779, 2015